Disorientasi Jual-Beli Kelapa Sawit Mentah di Desa Aek Goti Kecamatan Silangkitang: (Tinjauan Hukum Islam) - Prayetno, Dwi; Putra, Johan Septian (AT-TASYRI': JURNAL ILMIAH PRODI MUAMALAH, 2024)
There is an act of buying and selling between collectors (toke) and palm oil farmers who buy and sell immature palm fruit at the price set by the collector (toke) and this selling price is very different from the price of ripe palm oil, which is where the price of palm fruit is following the retail price circulated by the factory and agreed upon by the collectors (toke-toke) in the area around Aek Goti village, Silangkitang sub-district, then with this activity various actions have emerged that are beyond The limit is due to economic factors that exist in the community of Aek Goti Village, Silangkitang District, so that violations such as theft of oil palm fruit often appear because the collectors (toke) always collect the fruit that comes even though it is not known where it comes from, even though the fruit is it's not yet ripe. And here the author wants to harmonize this with Islamic law. In this writing, the author uses a qualitative field method (Field Research), so the author tries to find informants or sources related to the research problem. The author immediately went out into the field to obtain the required data by visiting the collectors (toke) and farmers who own oil palm plantations in Aek Goti Village, Silangkitang District.